PENGARUH KUALITAS LAYANAN AKADEMIK TERHADAP KEPUASAN MAHASISWA DI STIK IMMANUEL BANDUNG - Ekawati, Dian (Jurnal Ilmu Kesehatan Immanuel, 2018)
The purpose of this study was to determine the effect of service quality consisting of: tangible evidence, reliability, responsiveness, assurance  and empathy on student satisfaction at STIK Immanuel Bandung, and to find out Which service quality variable has the dominant influence on student satisfaction at STIK Immanuel Bandung. This is very important considering the quality of higher education education services often gets the spotlight and criticism from various parties because it is considered to have poor performance. This study is a causal study, namely research that seeks to find a causal relationship between the independent variable (independent) and the dependent variable (dependent). To do a causal analysis, the data analysis technique that can be used is multiple linear regression. The results showed that there was a positive influence on service quality factors consisting of: tangible evidence, reliability (responsiveness), responsiveness, assurance (Assurance) and empathy (Empathy) having a partial effect on the satisfaction of STIK Immanuel Bandung students) . Service factors Empathy and Tangible have the most dominant influence on satisfaction of STIK Immanuel Bandung students. Suggestions from researchers are to maintain service quality so far because service quality factors have been shown to have positive impacts on student satisfaction, need to provide training to academic staff both educators and education staff in improving service quality, looking at efforts to fulfill services from empathy and physical facilities in serving customers to be able to realize quality service quality, and improve services, especially regarding the problem of speed of complaint handling